2008
DOI: 10.1177/0146167207311198
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Interpersonal Perceptions, and Happiness in Social Interactions

Abstract: The authors examined cultural differences in interpersonal processes associated with happiness felt in social interactions. In a false feedback experiment (Study 1a), they found that European Americans felt happier when their interaction partner perceived their personal self accurately, whereas Asian Americans felt happier when their interaction partner perceived their collective self accurately. In Study 1b, the authors further demonstrated that the results from Study 1a were not because of cultural differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 38 publications
(53 reference statements)
4
53
1
Order By: Relevance
“…In contrast to Western understandings of emotional states such as "happiness," which tend to be located at the level of the individual (Oishi, Koo, & Akimoto, 2008;Uchida & Kitayama, 2009), narratives from women contributing to this study confirmed these types of emotional states were embedded in, and inseparable from, family and wider social relations. Hence, women's reluctance, reported in our study, to voice negative feelings or emotions for fear of provoking marital disharmony and bringing shame on the family.…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast to Western understandings of emotional states such as "happiness," which tend to be located at the level of the individual (Oishi, Koo, & Akimoto, 2008;Uchida & Kitayama, 2009), narratives from women contributing to this study confirmed these types of emotional states were embedded in, and inseparable from, family and wider social relations. Hence, women's reluctance, reported in our study, to voice negative feelings or emotions for fear of provoking marital disharmony and bringing shame on the family.…”
Section: Discussioncontrasting
confidence: 76%
“…Toward the end of the survey, participants indicated the degree to which they felt understood and misunderstood by others by responding to “During your interaction with others today, to what extent did you feel understood by others?” ( M = 4.94, SD = 1.23) followed by “And, to what extent did you feel misunderstood by others?” ( M = 2.68, SD = 1.29) on a 7-point Likert scale (1 = not at all , 7 = a lot ; adapted from Oishi et al, 2008). On average, these two items were correlated at −.38 ( SD = .37) across individuals over the 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Research on close relationships and social support predicates that people should feel happier and healthier when they are surrounded by others who understand their needs and values. For example, people experience greater positive affect when they feel that their partner understands them (Oishi, Koo, & Akimoto, 2008) and shares their joy for positive life events (Gable, Reis, Impett & Asher, 2004). Perceiving close others to be responsive and understanding of a stressful experience mitigates its negative impact on one’s health and subjective well-being (Sarason, Sarason, & Gurung, 1997).…”
mentioning
confidence: 99%
“…Studies have also found that people experience greater positive affect, greater life satisfaction, and fewer physical symptoms when they feel more understood by others (Lun, Kesebir, & Oishi, 2008;Oishi, Koo, & Akimoto, 2008). Several studies of caregivers of patients with long-term illnesses have reported that the caregivers' feelings of appreciation were linked with their positive experiences from caregiving (Farran, Keane-Hagerty, Salloway, Kupferer, & Wilken, 1991), and that the caregivers valued their patients' affection and appreciation (Motenko, 1989).…”
Section: Introductionmentioning
confidence: 99%